Constitutional courts and social transformation in Colombia and South Africa - (:unkn) unknown (My University, 2023)
The Constitutional Courts of Colombia and South Africa were created in the 1990s after ambitious constitutional transitions, following political regimes that were deemed exclusionary and inegalitarian. A power of judicial review has been conferred to the two courts along with the guardianship of two texts presenting values, fundamental rights and social rights. In both countries as well as in the field of comparative law, it became a commonplace to speak of a new constitutionalism of the South or a transformative constitutionalism. The two tribunals are close to a form of power named “gouvernement des juges” since the rise of constitutional justice in the twentieth century, with the distinctive feature of a social transformation through law. A critical and contextualist study should qualify this spontaneous presentation by emphasising the diversity of influences and relations that could explain the jurisprudence of the two courts. A radical judicial activism can be qualified as a power, although limited, and the participation to a reconfiguration of the relationship between law and politics. Both courts have produced a discourse on social transformation and on the world, a discourse which is itself part of the discourses on constitutionalism. Judges, politicians, activists and academics have contributed to a form of constitutionalism in which the language ot law and the discursive authority of courts are central.
Keywords: African Research